Mastering Apache Cassandra 3.x : An expert guide to improving database scalability and availability without compromising performance, 3rd Edition /: An expert guide to improving database scalability and availability without compromising performance, 3rd Edition. (2018) - Ploetz, Aaron; Malepati, Tejaswi; Neeraj, Nishant
No abstract available